Respostas
respondido por:
0
3x - y = y ( 1 )
x + y = 2 ou y = 2 - x ******
substitui em 1
3x - ( 2 - x) = ( 2 - x)
3x - 2 + x = 2 - x
4x - 2 = 2 - x
4x + x = 2 + 2
5x = 4
x = 4/5 =0.8 *****
y = 2 - ( 0.8 )
y = 1,2 *****
x + y = 2 ou y = 2 - x ******
substitui em 1
3x - ( 2 - x) = ( 2 - x)
3x - 2 + x = 2 - x
4x - 2 = 2 - x
4x + x = 2 + 2
5x = 4
x = 4/5 =0.8 *****
y = 2 - ( 0.8 )
y = 1,2 *****
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás